Role and Impact of Profit and Non-Profit Social Enterprises in India - Budhedeo, Shradha Hitesh; Doshi, Parinda Viral (Prabandhan: Indian Journal of Management, 2015)
India is gradually making its presence felt across the globe. It is one of the fastest growing economies in the world today. India projects promising economic indicators in terms of rising GDP and per capita income, but has gloomy social indicators. There is a huge gap between the economic and social status of the nation. There is an urgent need to fill this gnawing gap and elevate the social scenario of the country. There are serious concerns relating to poverty, health, education, water, sanitation, food, housing, and environment in the society which need to be addressed. Profit motivated and not-for-profit social enterprises/entrepreneurs have taken giant strides in the social sector with an aim to fulfil basic social needs of the deprived masses. Social entrepreneurs may not be the complete solution to India’s massive problems, but their intervention definitely facilitates in combating some of the critical social issues in the country. They provide innovative sustainable solutions to the nation’s entrenched social problems and accelerate human development. In this backdrop, the present study endeavored to explore the different social entrepreneurship initiatives in the direction of bridging the socioeconomic gap. The study reviewed the role, impact, contribution, and achievements of these concerted efforts in the Indian social sector.